2010
DOI: 10.1021/jp910592y
|View full text |Cite
|
Sign up to set email alerts
|

UV-Induced Chromatism of Polydiacetylenic Assemblies

Abstract: Highly ordered lamellar polydiacetylene nanocomposites are synthesized by assembling polydiacetylene and azobenzene through a ready solution process. The trans-to-cis transition of azobenzene under UV light induces a conformational change of polydiacetylene with a color change from blue to red.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…UV-induced chromatism has been reported to be powered by the [2+2] cycloaddition of cyano-stilbene derivatives [12] (on-off change) and the transto-cis transition of azobenzene (from blue to red). [13] To the best of our knowledge, the result we report is the first example of UV-induced chromatism that shows white-light PL emissions.Our previous studies [11d, e] have demonstrated that RhB molecules on silica nanoparticle surfaces could exhibit white-light emissions (under excitation at 365 nm), which is different from the yellow emission of the free RhB molecules in solutions. The change in the PL-emission colours has been attributed to the aggregation of RhB molecules in The chromatism of the UV-irradiated RhB solutions observed herein is similar to the PL behaviour of the RhBanchored silica nanoparticles.…”
mentioning
confidence: 69%
“…UV-induced chromatism has been reported to be powered by the [2+2] cycloaddition of cyano-stilbene derivatives [12] (on-off change) and the transto-cis transition of azobenzene (from blue to red). [13] To the best of our knowledge, the result we report is the first example of UV-induced chromatism that shows white-light PL emissions.Our previous studies [11d, e] have demonstrated that RhB molecules on silica nanoparticle surfaces could exhibit white-light emissions (under excitation at 365 nm), which is different from the yellow emission of the free RhB molecules in solutions. The change in the PL-emission colours has been attributed to the aggregation of RhB molecules in The chromatism of the UV-irradiated RhB solutions observed herein is similar to the PL behaviour of the RhBanchored silica nanoparticles.…”
mentioning
confidence: 69%
“…Inorganic materials and polymer materials such as tungsten oxide [54], liquid crystal molecules [55], polydiacetylene (PDA) [56][57][58], poly [1-phenyl-2-(p-trimethylsilyl) phenylacety-lene] (PTP), polyurethane (PU), polyaniline (PANI), polypyrrole (PPy) and polydimethylsiloxane (PDMS) can be combined with ACNT to obtain performance of change color in response to electricity.…”
Section: Electrochromismmentioning
confidence: 99%
“…2 Chromatic polydiacetylene/silica synthesized from diacetylene-bridged silsesquioxanes Polydiacetylene (PDA) has been extensively investigated as sensing materials due to the unique chromatic transition, typically from blue to red in response to environmental stimuli [46]. Various PDA materials such as vesicles, films, and nanocomposites have been fabricated, and their chromatic responses to a broad spectrum of external stimuli (temperature, pH, ion, solvent, stress, and ligand interactions) have been reported.…”
Section: Introductionmentioning
confidence: 99%